2000
DOI: 10.1103/physrevb.62.r11985
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of an ordered state of spins and holes in single-crystalLa2xSrx

Abstract: Zero-field ͑ZF͒ and longitudinal-field ͑LF͒ muon spin relaxation (SR) measurements have been carried out in the overdoped single crystals of La 2Ϫx Sr x Cu 1Ϫy Zn y O 4 with xϭ0.21, yϭ0 and 0.01. In the case of the Zn-substituted crystal with xϭ0.21 and yϭ0.01 in which the high-T c superconductivity is almost suppressed, the ZF-and LF-SR measurements have revealed the existence of a static ordered state of Cu spins at low temperatures below 2 K. No clear coherent precession of the muon spin has been observed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
(31 reference statements)
2
8
0
Order By: Relevance
“…Although c also shows metallic temperature dependence in the overdoped LSCO at ambient pressure, the low temperature upturn of c at high pressures is reported by Goko et al 25) In addition, we can not overlook the effect of the apical oxygen, which will give rise to stronger perturbation on the electronic state of confined carriers in the CuO 2 planes with increasing pressure. The other is that x ¼ 0:22 is close to a critical Sr concentration reported by Watanabe et al 26) They measured the muon spin relaxation of Zn doped LSCO with x ¼ 0:21, suggesting the possible existence of a spin/charge ordered state.…”
Section: Discussionsupporting
confidence: 73%
“…Although c also shows metallic temperature dependence in the overdoped LSCO at ambient pressure, the low temperature upturn of c at high pressures is reported by Goko et al 25) In addition, we can not overlook the effect of the apical oxygen, which will give rise to stronger perturbation on the electronic state of confined carriers in the CuO 2 planes with increasing pressure. The other is that x ¼ 0:22 is close to a critical Sr concentration reported by Watanabe et al 26) They measured the muon spin relaxation of Zn doped LSCO with x ¼ 0:21, suggesting the possible existence of a spin/charge ordered state.…”
Section: Discussionsupporting
confidence: 73%
“…This is interpreted as a result of the strong pinning effect of Zn on the dynamically fluctuating stripes of spins and holes [8,9]. Similar effects of Zn on the Cu-spin dynamics has been observed in the hole-doped Bi 2 Sr 2 Ca 1- [10,11] and YBa 2 Cu 3-2y Zn 2y O 7-δ [12] as well.…”
Section: Introductionsupporting
confidence: 69%
“…The temperature dependence of the spectra is similar to one another. No impurity-induced slowing down of the Cu-spin fluctuations is detected for moderately oxygen-reduced samples of the small and large δ, which is very different from the results of the hole-doped high-T c cuprates [6][7][8][9][10][11][12]. This may be understood in two ways.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…In the Zn-substituted crystal with x = 0.21, the electrical resistivity exhibits upturn at low temperatures below ~ 80 K and the temperature dependence of the thermoelectric power is also anomalous. Prom the /iSR measurements, 18,26 it has been found that the magnetic correlation is enhanced at low temperatures below 3.5 K in the 1% Zn-substituted crystal with x = 0.21, while it is enhanced below 0.8 K in the Zn-free one. Prom the JJLSR measurements of the 1% Zn-substituted crystal with x = 0.21 under LF, moreover, it has been found that the muon-spin depolarization rate exhibits a nearly squareroot LF-dependence at 3.0 K as observed in the Bi-2212 sample with p ~ 1/8 and that all of the Cu spins are frozen at 0.30 K. These results suggest that the dynam- ical stripe-order is slowly fluctuating at 3.0 K and changes to a static short-range stripe-order at 0.30 K. According to the recent experiment of the elastic neutron-scattering by Kimura et a/., 27 incommensurate peaks around (7r,7r), which are similar to those observed from the inelastic neutron-scattering experiment in the overdoped region, have been observed in the 1% Zn-substituted crystal with x = 0.21.…”
Section: New Anomaly At X = 021 Inmentioning
confidence: 98%